Relationship between protein energy malnutrition and social maturity in children aged 1-2 years - Nurhayati Nurhayati; Soetjiningsih Soetjiningsih; I Ketut G. Suandi (Indonesian Pediatric Society, 2002)
Background Protein energy malnutrition (PEM) affects physical, psychological, and social development.Objective To investigate the relationship between PEM and social maturity in children aged 1-2 years.Methods We carried out a cross-sectional study at Child Health Outpatient Clinic, Sanglah Hospital, betweenApril-September 2000. We included children living with their parents, with no handicap or chronically ill condition. Data were collected by using structured questionnaires. Nutritional status was determined based on WHO-NCHS standard, while social maturity was measured by Vineland social maturity scale.Results Of the 200 subjects analyzed, the mean age was 16.9 months (SD 3.8), body weight 10.2 kg (SD 1.7) and social quotient (SQ) score 94.3(SD 10.6). There was a significant correlation between SQ and PEM (B-7.5, CI 95%-10.6;-4.3, p<0.001) parents' occupation (B4.9, CI 95% 2.2-7.7, P<0.001) and mothers' education (B4.2,CI 95% 1.0-7.4, P<0.001).Conclusion This study revealed that the more severe the PEM, the lower the SQ, while the better the education and occupation, the higher the SQ was.